THE ROLE OF THE SHARIAH BOARD IN PROTECTING AND PROMOTING THE STAKEHOLDERS’ RIGHTS IN BAHRAIN - Hassan, Mazin; Besar, Azrin; Jaidin, Halida (Universitas Islam Indonesia, 2024)
Islamic corporate governance (ICG) is aimed at maintaining Shariah compliance in the Islamic finance industry. Thus, it seeks to achieve the strategic objectives of Shariah, that are maqāṣid al-Shariah. Accordingly, it should protect and promote the stakeholders’ rights if these rights are recognized by Shariah. However, the literature on the role of Islamic corporations in protecting and promoting the rights of the stakeholders is not sufficient in contrast to conventional corporate governance (CCG). This paper fills this gap by looking into how far the Shariah board in the Kingdom of Bahrain protects and promotes the rights of the bank, customer, and state with reference to the maqāṣid of Shariah, specifically, the maqāṣid of wealth as well as the laws of the Kingdom of Bahrain. After the discussion, it can be concluded that the Shariah board in the Kingdom of Bahrain significantly protects and promotes the financial rights of the bank, the customer, and the state but it failed in some aspects of law and maqaṣid of Shariah specifically the circulation, and specification of wealth under the wealth maqṣaḍ.